Efektivitas Penanganan Covid-19 dan Dampaknya pada Hasil Pemilihan Umum: Studi Kasus Pengaruh Penerapan Four-Pronged Strategy Pemerintahan Presiden Moon Jae-in dan Civic Duty Masyarakat Korea Selatan terhadap Kemenangan Democratic People’s Party of Korea pada Pemilihan Umum Legislatif Korea Selatan Tahun 2020 - Siti Aldira (LITERATUS, 2021)
The Covid-19 pandemic has disrupted elections in various countries, decreased voter participation, and increased the potential for virus transmission that threatens public health—one of the countries holding elections during the Covid-19 pandemic in South Korea. In contrast to most other election organizing countries during the pandemic, the South Korean Legislative Election in 2020 became a legislative election with the highest turnout of voters reaching 66.2 percent. The election was won by the Democratic People's Party of Korea as the party that carries President Moon Jae-in. This study discusses the effect of the four-pronged strategy used by President Moon Jae-in in tackling Covid-19 on the victory of the Democratic People's Party of Korea. This study will also discuss the high civic duty of the South Korean community, which affects the high turnout of voters, regardless of elections held during a crisis. This study finds that despite the poor assessment of economic policies, foreign relations, and political scandals in the administration of President Moon Jae-in, crises are considered to have higher urgency and become the main indicator of a society in conducting retrospective assessments. This is supported by the public’s views, who view the Covid-19 pandemic as a national crisis, and participating in elections is considered a form of nation-saving duty. The high voter turnout and the effectiveness of the four-pronged strategy affected the victory of the Democratic People's Party of Korea in the 2020 South Korean Legislative Elections.